Perceived discrimination and cognitive function among older Puerto Ricans in Boston: The mediating role of depression. (23rd April 2022) - Wang, Kaipeng; Maglalang, Dale Dagar; Woo, Bongki; De Fries, Carson M.; Hasche, Leslie K.; Falcón, Luis M.
Abstract: Objectives: To examine (1) the association between perceived discrimination, including everyday perceived discrimination and major lifetime perceived discrimination, and cognitive function and (2) the mediating role of depression between discrimination and cognitive function among older Puerto Ricans. Methods: Data came from the Boston Puerto Rican Health Study, collected from 562 Puerto Ricans aged 60+. Structural Equation Modelling was used to examine the association between discrimination and cognitive function and the mediating effect of depression. Results: Everyday perceived discrimination was negatively associated with cognitive function, which was fully mediated by depression. Major Lifetime perceived discrimination was not associated with cognitive function. Conclusions: The findings contribute new information regarding the impact of perceived discrimination on cognitive function among older Puerto Ricans and underscore the importance of assessing experiences of discrimination to prevent depression and cognitive decline in this population. Key points: Everyday perceived discrimination was negatively associated with cognitive function, which was fully mediated by depression Major Lifetime perceived discrimination was not associated with cognitive function